MAINTENANCE SERVICE CONTRACT INVOLVING TWO PARTIES (CASE STUDY: HEAVY EQUIPMENT LOCATED IN EAST KALIMANTAN PROVINCE) - Adhipura, Panji
Coal price movements tend to strengthen throughout 2021, making heavy equipment sales as a means of transportation in the mining business increase significantly (equipmentindonesia.com). In line with the sales, the maintenance of heavy equipment must also be carried out to avoid losses that can reach US$ 24 million per day (Husniah, 2011). In this paper, for economic reasons, the consumer carries out maintenance responsibilities within a maintenance service contract (MSC) with the agent (manufacturer/external agent). This paper aims to model a heavy equipment maintenance contract that maximizes the profits of manufacturers and agents. MSC modeling begins by explaining the warranty and MSC policy, then modeling failure, maintenance, and profit expectations for each party. For the failure modeling, we study failure data from a manufacturer period of 2007-2020. After the data was limited to only one consumer, that were investigated further by displaying descriptive statistics and conducting distribution tests, the data obtained following the NHPP and Weibull distribution. Furthermore, preventive maintenance modelling is carried out periodically and affects failure distribution by reducing the failure intensity function. Finally, a model of expected profit for each party is built from the two options provided by the manufacturer. The Stackelberg game theory then solves the decision problem to ensure maximum profit for each party.